Female technician at work in Dearborn laboratory facility - Dearborn Chemical Company (1924)
General view of an unidentified female laboratory technician preparing a water sample for analysis at the Dearborn Chemical Company's 35th Street Laboratory. Founded in 1887, the Dearborn Chemical Company was a corporate ancestor of BetzDearborn, Incorporated best known for manufacturing water treatment chemicals for use in boilers and cooling towers.
Keywords: Women in science; Chemical industry; Laboratories; Water purification chemicals industry; Corporations; Women employees; Dearborn Chemical Company; Scientific apparatus and instruments